2022
DOI: 10.1001/jamanetworkopen.2022.11677
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison of Medical Cannabis Use Reported on a Confidential Survey vs Documented in the Electronic Health Record Among Primary Care Patients

Abstract: This survey study compares the use of cannabis for medical purposes as reported in electronic health records (EHRs) with use reported in a confidential survey.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 66 publications
6
36
0
Order By: Relevance
“…Despite increasing trends, a very small portion of notes overall documented cannabis use (<2%), which for the most part contained insufficient information (i.e., duration, frequencies, amount). These findings are in line with recent studies indicating discrepancies between patient reported cannabis (e.g., surveys) and cannabis use documentation in health records [30], while showing a much lower rate than those previously reported.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Despite increasing trends, a very small portion of notes overall documented cannabis use (<2%), which for the most part contained insufficient information (i.e., duration, frequencies, amount). These findings are in line with recent studies indicating discrepancies between patient reported cannabis (e.g., surveys) and cannabis use documentation in health records [30], while showing a much lower rate than those previously reported.…”
Section: Resultssupporting
confidence: 92%
“…However, whether the use of cannabis has downstream effects on the treatment choices and outcomes requires further evaluations. The high prevalence of cast/splint procedures, often done for treatment of bone fractures, among cannabis users along with prior reports of changes in bone remodeling due to cannabis use [3,4,30,[33][34][35][36][37] further highlight the importance of proper cannabis use documentation to improve treatment outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…Using EHR data, 5000 patients were randomly sampled for the survey. As detailed elsewhere, 35 we oversampled for higher frequency of past-year cannabis use (58% daily, 24% weekly, 7% monthly, 6% less than monthly, 6% no use) and ensured 35% of the sample were individuals who belonged to minoritized racial and ethnic groups to obtain representation from important subgroups.…”
Section: Methodsmentioning
confidence: 99%
“… 55 Comparisons of the eligible primary care population, eligible survey sample, nonrespondents, respondents, and the weighted primary care sample have been previously reported. 35 …”
Section: Methodsmentioning
confidence: 99%
“…In the Original Investigation titled “Comparison of Medical Cannabis Use Reported on a Confidential Survey vs Documented in the Electronic Health Record Among Primary Care Patients,” 1 published May 23, 2022, there was an error in the Role of the Funder/Sponsor. This section should have stated that a National Institute on Drug Abuse–appointed Data and Safety Monitoring Board (DSMB) reviewed the design and conduct of the study.…”
mentioning
confidence: 99%